Joint association of statins and testosterone replacement therapy with cardiovascular disease among older men with prostate cancer: SEER-Medicare 2007–2015. (August 2022) - Lopez, David S.; Kim, Hyunkyoung; Polychronopoulou, Efstathia; Taha, Shaden; Tsilidis, Konstantinos K.; Villasante-Tezanos, Alejandro; Peek, M. Kristen; Gilani, Syed; Khera, Mohit; Baillargeon, Jacques; Kuo, Yong-Fang; Canfield, Steven
Abstract: Background: Use of statins and testosterone replacement therapy (TTh) have been independently linked with prostate cancer (PCa) and cardiovascular diseases (CVD). However, there is a research gap about the joint association of statins and TTh with CVD among PCa survivors and a matched cancer-free cohort. Methods: In SEER-Medicare 2007–2015 (N = 35, 990 men), we identified 17, 995 PCa survivors, and 17, 995 age- and index-matched cancer-free men. Pre-diagnostic prescription of statins and TTh was ascertained for this analysis and examined in two matched cohorts. Weighted multivariable-adjusted conditional logistic regression models were used to evaluate the independent and joint associations of statins and TTh with CVD. Results: We found that independently statins (OR = 0.48, 95% CI: 0.44–0.53) and TTh (OR = 0.74, 95% CI: 0.0.61–0.90) were each inversely associated with CVD in the overall sample. TTh plus statins was inversely associated with CVD (OR = 0.50, 95% CI: 0.36–0.70, P interaction = 0.03). Similar associations were observed among the matched cancer-free cohort. Among PCa survivors, only statins (OR = 0.62, 95% CI: 0.56–0.68) and combination of TTh plus statins (OR = 0.63, 95% CI: 0.44–0.90) were inversely associated with CVD, but not the independent use of TTh. Conclusion: Pre-diagnostic use of statins and TTh, independent or in combination, were inversely associated with CVD in the overall and cancer-free populations, but among PCa survivors it was mainly use of statins, not TTh. Greater reduced effects on CVD were observed with statins or in combination with statins, but not with TTh. Future studies need to confirm these associations among older men with aggressive PCa. Highlights: In the overall population, independently and jointly the use of statins and TTh reduced the incidence CVD. Among prostate cancer survivors, use of statins and the joint association of statins and TTh reduced the incidence of CVD. Among the cancer-free population, independently and jointly the use of statins and TTh reduced the incidence of CVD This is the first study that quantifies the joint association of statins and TTh with CVD among prostate cancer survivors.